High gastric ulcus surgical tactics - Suiffet, Walter (Cirugía del Uruguay, 1983)
High gastric ulcus surgical tactis is analized taking into account incidence and lo ca tion. Frecuency varíes between 0.6 to 20.4% of ali G.U. It appears at an older age than other locations of G. U. The indication for surgical treatment is the same as any G.U. The surgical tactics include resection and non resection procedures. Consideríng advantages and inconveniences, the author prefers resection procedures i.e. partial distal sleeve gastrectomy or partial proximal gastrectomy with pyloroplasty and an antirreflux procedure added. The other methods will serve for exceptional situations.